BUDAYA ORGANISASI PERUSAHAAN ASURANSI JIWA DI INDONESIA - Edward Efendi Silalahi (Universitas Mercu Buana, 2017)
Abstract. This research aims at exploring organizational culture in life insurancecompany in Indonesia, i.e. Prudential Indonesia and JIWASRAYA and its contributionto financial performance, This study used a qualitative approach with case studyresearch, using exploratory and descriptive research design supported by successiveapproximation of technical data analysis. The research found six proposition asfollows: 1) Consistent and appropriate strategy with the system and business orientationwill determine the success of the corporate,, 2) Planning of Human Resourcesintegrated with corporate plan will improve the affectivity of Human Resourcesmanagement, 3) Organization structure and system in accordance with internal andexternal environment will support development of business, 4) Working process ofcustomer satisfaction and result-oriented is needed to support development of corporatebusiness, 5) Organization culture implemented in the course of action has strategic roleto improve corporate performance, and 6) Consistent socialization and application ofcorporate culture will give contribution on financial performance.Keywords: life insurance company, organizational culture, qualitative, case study andsuccessive approximation